2018
DOI: 10.1002/cam4.1900
|View full text |Cite
|
Sign up to set email alerts
|

A novel lncRNA‐miRNA‐mRNA network analysis identified the hub lncRNA RP11‐159F24.1 in the pathogenesis of papillary thyroid cancer

Abstract: Papillary thyroid cancer (PTC) is one of the most common cancers worldwide, and its carcinogenesis is influenced by a complex network of gene interactions. In this study, the microarray expression profile was re‐annotated into a lncRNA‐mRNA biphasic profile. LncRNA‐mRNA interactions were confirmed by established miRNA‐RNA data and hypergeometric test. Then, a PTC‐related lncRNA‐miRNA‐mRNA network (PTCRN) was constructed by integrating differentially expressed genes with the RNA‐RNA networks. The new network co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…MicroRNAs are small noncoding RNAs which could negatively regulate the expression of the target genes by directly binding their 3′-UTRs [24]. It has been found that the deregulation of miRNA expression is a common feature of many types of human cancers, including thyroid cancer [25,26]. Accumulated evidence has demonstrated that the aberrant expression of miRNAs plays crucial roles in cancer initiation and progression [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs which could negatively regulate the expression of the target genes by directly binding their 3′-UTRs [24]. It has been found that the deregulation of miRNA expression is a common feature of many types of human cancers, including thyroid cancer [25,26]. Accumulated evidence has demonstrated that the aberrant expression of miRNAs plays crucial roles in cancer initiation and progression [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…miR-485 showed a significantly lower expression in PTC tissues as compared with normal tissues (26). As the targets of miR-485, 47 mRNAs were associated with several biological processes, especially pathways in cancer.…”
Section: :1 119 Clinical Studymentioning
confidence: 96%
“…It was recently reported that overexpression of MALAT1 could sponge miR-429 and regulate cervical cancer pathogenesis in vivo and in vitro (54), while the associations between MALAT1 and RUNX3 remain unclear. However, the role of RP11-54O7.3 has not yet been fully elucidated, and the association between RP11-54O7.3 and RUNX3 remains unknown (55,56). These results indicate that RUNX3 may affect the expression of lncRNAs , which may be associated with cervical cancer in vitro .…”
Section: Discussionmentioning
confidence: 99%